Predictive and prognostic potential of pretreatment 68Ga-PSMA PET tumor heterogeneity index in patients with metastatic castration-resistant prostate cancer treated with 177Lu-PSMA - Assadi, Majid; Manafi-Farid, Reyhaneh; Jafari, Esmail; Keshavarz, Ahmad; Divband, GhasemAli; Moradi, Mohammad Mobin; Adinehpour, Zohreh; Samimi, Rezvan; Dadgar, Habibollah; Jokar, Narges; Mayer, Benjamin; Prasad, Vikas (Frontiers in Oncology, 2022)
Introduction This study was conducted to evaluate to the predictive values of volumetric parameters and radiomic features (RFs) extracted form pretreatment 68Ga-PSMA PET and baseline clinical parameters in response to 177Lu-PSMA therapy. Materials and methods In this retrospective multicenter study, mCRPC patients undergoing 177Lu-PSMA therapy were enrolled. According to the outcome of therapy, the patients were classified into two groups including positive biochemical response (BCR) (≥ 50% reduction in the serum PSA value) and negative BCR (< 50%). Sixty-five RFs, eight volumetric parametrs and also seventeen clinical parameters were evaluated for prediction of BCR. In addition, the impact of such parameters on overall survival (OS) was evaluated. Results 33 prostate cancer patients with a median age of 69 years (range: 49-89) were enrolled. BCR was observed in 22 cases (66%), and 16 cases (48.5%) died during the follow-up time. The results of Spearman correlation test indicated a significant relationship between BCR and treatment cycle, administered dose, HISTO energy, GLCM entropy, and GLZLM LZLGE (p<0.05). In addition, according to the Mann-Whitney U test, age, cycle, dose, GLCM entropy, and GLZLM LZLGE were significantly different between BCR and non BCR patients (p<0.05). According to the ROC curve analysis for feature selection for prediction of BCR, GLCM entropy, age, treatment cycle, and administered dose showed acceptable results (p<0.05). According to SVM for the assessing of the best model for predication of response to therapy, GLCM entropy alone showed the highest predictive performance in treatment planning. For the entire cohort, the Kaplan-Meier test revealed a median OS of 21 months (95% CI: 12.12-29.88). The median OS was estimated at 26 months (95% CI: 17.43-34.56) for BCR patients and 13 months (95% CI: 9.18-16.81) for non BCR patients. Among all variables included in the Kaplan Meier, only response to therapy was statistically significant (p=0.01). Conclusion This exploratory study showed that heterogeneity parameter of pretreatment 68Ga-PSMA PET images might be a potential predictive value for response to 177Lu-PSMA therapy in mCRPC; however, further prospective studies need to be carried out to verify these findings.